Compliance with smoke-free legislation and smoking behaviour: an observational field study in Karachi, Pakistan - Moorpani, Komal; Shaikh, Shiraz; Tariq, Hira (Journal of the Pakistan Medical Association, 2024)
Objectives: To observe compliance with smoke-free law at different public places in an urban setting. Method: The cross-sectional study was conducted from January to June 2022 after approval from the ethics review board of Jinnah Sindh Medical University, Karachi, at public places, including public and private offices, health institutions, education institutions, malls, markets and eateries, in 5 districts of Karachi. Boundary, entrance, waiting areas/corridors, toilet areas and eating areas were assessed using a checklist for smoke-free law compliance. Places were considered compliant if no smoking activity, cigarette butt litter or ashtrays was found. Data was analysed using SPSS 21. Results: Out of 400 places observed, there were 80(20%) in each of the 5 districts. Overall, 36(44%) of the venues showed indoor compliance and 10(12%) showed outdoor compliance. Presence of cigarette butts was observed at 350(87.5%) outdoor places around the boundary of the premises. Only 38(9.5%) of the places had no smoking boards outdoors and at the entrance, with 16(4%) being clearly visible. Also, 27(43%) of educational institutions had a cigarette shop within 50 metres of the boundary. Conclusion: The city was found to have poor implementation of smoke-free laws, especially for outdoor areas, exposing the public to constant second-hand smoke. Key Words: Smoking, Second-hand smoke, Smoke-free policies, Karachi.